From margin to margin: The depiction of Roma in Romanian cinema after 1989 -- A historical overview - Toderici, Radu (Romano džaniben, 2025)
This essay outlines a concise history of Romanian cinema over the last three decades, in relation to the cinematic representation of the Roma, one of Romania's largest ethnic minorities. Starting with the scarcity of representations of Romani characters in Romanian cinema until the fall of the socialist regime, a phenomenon that indirectly reflects the systematic marginalization and discrimination of this minority in Romania, the analysis focuses on films produced after 1989 that reproduce, reinterpret or renegotiate local and stereotypical images of Romani ethnic groups. These filmic representations are then interpreted and classified from a diachronic perspective.
Keywords: Romanian cinema; representation of ethnic minorities; Roma minority; inclusion; discrimination